Hubungan Berpikir Kritis dengan Hasil Belajar Pada Mata Pelajaran Fisika, Kimia, Biologi dan Matematika Ditinjau dari Meta Analisis - Jumriani Sultan; Slamet Suyanto; Zulfa Safira Ibrahim (Postgraduate, University of Mataram, 2023)
Critical thinking is an important element in understanding a subject of Physics, Chemistry, Biology, and Mathematics. Learning outcomes are closely related to critical thinking skills. This study used the meta-analysis method assisted by the JASP program with the aim of determining the relationship between critical thinking and learning outcomes in Physics, Chemistry, Biology, and Mathematics. Meta-analysis is used by reviewing research articles published in journals in the range of publication years starting from 2018 to 2023 which are obtained purposively so that there are 20 articles. The results of this meta-analysis show that the relationship between critical thinking and learning outcomes of Physics, Chemistry, Biology, and Mathematics subjects is included in the high category indicated by a correlation effect size (rE) value of 0.891 with a p-value of less than 0.01 at a 95% confidence level